Definite Discourse–New Reference in L1 and L2: A Study of Bridging in Mandarin, Korean, and English. Issue 3 (September 2014) - Crosthwaite, Peter Robert
<x xml:space="preserve">Abstract</x> Definite expressions may be used to introduce a referent into discourse when their familiarity between speaker and listener can be inferred, a strategy known as bridging. However, for a number of reasons, bridging may be difficult to acquire compared to the acquisition of indefinite introductions for noninferable referent types, with the native language of the second language (L2) learners suggested to be a major factor influencing L2 acquisition. Two experiments were conducted into the use of bridging, using a controlled picture sequence where neutral, weakly, or strongly inferable referents were to be introduced. The first study investigated native speaker data from English, Mandarin Chinese, and Korean, and the second study focused on a cross‐section of learner data from Mandarin and Korean L2 English learners from six proficiency levels ranging from A1 (Basic user) to C2 (Proficient user) of the Common European Framework. The native results show that the three languages introduce inferable referents in markedly different ways: definite articles for English, omission of numeral + classifiers before the noun for Mandarin, and with Korean making no apparent distinction for inferability in terms of noun‐phrase form. The L2 results show that the acquisition of the definite article + noun construction to introduce inferable referents in L2 English occurs at lower Common European Framework levels for the Mandarin group than the Korean group. Therefore, it is claimed that Mandarin L2 English learners may have less difficulty mapping L2 syntactic form to pragmatic function in their L2 narrative production than their Korean counterparts, as a possible consequence of positive transfer from their native language.